Connecting Land Ethics and Entrepreneurship Through Experiential Learning in Bobwhite Centric Outdoor Education Program - Greta M. Bowling; Ashleigh P. Tynes; Kelly S. Reyna (National Quail Symposium Proceedings, 2017)
The majority of today’s youth have the ability to utilize consumer technology on a regular basis. This access has exacerbated the disconnect between adolescents and the natural environment by reducing the amount of time spent outdoors. To compound this disconnect, the continued use of traditional classroom settings along with the ‘‘sit-and-get’’ style of facilitation, widens the gap between inert knowledge and applied knowledge. The transformation from theory to practice witnessed in outdoor science, technology, engineering and mathematics (STEM) education has been shown to foster the assimilation and retention of STEM concepts. Therefore, educational institutions have begun to cultivate the implementation of experiential learning programs in order to provide the appropriate setting for students to establish relationships between theory and application. This study investigated the relationship between experiential learning and content information retention in a bobwhite centric outdoor education program in which participants were given the task of creating a habitat management plan for a tract of land by utilizing entrepreneurship skills acquired over the course of camp. The study participants consisted of north Texas youth and program facilitators. Pre- and post-assessments were administered on the first and last day of the program. The data indicate an increase in content information retention among participants in experiential settings. The results are consistent with similar studies that have analyzed experiential learning methodologies and their impact on data retention. We recommend that the experiential approach be further applied and tested in youth outdoor education programs.
Keywords: quail; northern bobwhite; entrepreneurship; experiential learning; land ethics; outdoor education program; STEM education